2012
DOI: 10.1161/circoutcomes.112.965111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Population Interventions to Improve Access to Reperfusion for ST-Segment–Elevation Myocardial Infarction in Australia

Abstract: Background-Improving timely access to reperfusion is a major goal of ST-segment-elevation myocardial infarction care. We sought to compare the population impact of interventions proposed to improve timely access to reperfusion therapy in Australia. Methods and Results-Australian hospitals, population, and road network data were integrated using Geographical Information Systems. Hospitals were classified into those that provided primary percutaneous coronary intervention (PPCI) or fibrinolysis. Population impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
0
27
0
4
Order By: Relevance
“…More emphasis needs to be given to delivering high-value prevention, wellness, screening and health maintenance services at the primary care level, integrated with relevant specialist providers. 93 Examples of such integrated practice include area-wide hospital substitution programs, 94 hospital-wide patient flow programs, 95 reconfigured emergency-acute care systems based on patient complexity and urgency, 96,97 collaborative primary care specialist teams based in non-hospital settings caring for patients with chronic diseases, 98,99 primary care substitution of specialist services 100 and multidisciplinary, patient-centred medical homes. 101 …”
Section: Convert Health Care Institutions Into Rapidly Learning Organmentioning
confidence: 99%
“…More emphasis needs to be given to delivering high-value prevention, wellness, screening and health maintenance services at the primary care level, integrated with relevant specialist providers. 93 Examples of such integrated practice include area-wide hospital substitution programs, 94 hospital-wide patient flow programs, 95 reconfigured emergency-acute care systems based on patient complexity and urgency, 96,97 collaborative primary care specialist teams based in non-hospital settings caring for patients with chronic diseases, 98,99 primary care substitution of specialist services 100 and multidisciplinary, patient-centred medical homes. 101 …”
Section: Convert Health Care Institutions Into Rapidly Learning Organmentioning
confidence: 99%
“…For example, strategies to preferentially direct patients to PCI hospitals are projected to increase access to PCI by 19% to 23% compared with a 3.7% increase in timely access to PCI by a 25% increase in PCI facilities nationwide. 14 The presence of shared features of inefficient dissemination between the United States and Australia, despite vastly different healthcare funding and regulatory structures, suggests that these factors alone are unlikely to be the mediators of such inefficiencies.…”
Section: Circ Cardiovasc Qual Outcomesmentioning
confidence: 99%
“…Decisions on implementation of technologies are often made on clinical efficacy alone, which partially reflects the lack of robust methods to incorporate population-specific factors into the decision-making process. The emergence of spatial data analysis techniques, as used by the authors and others, 12,14,15,18 may overcome such barriers. These methods, although still not widely used, have the capacity to detect, track, and predict the population impact of specific interventions.…”
Section: Circ Cardiovasc Qual Outcomesmentioning
confidence: 99%
“…A second article in this issue comes from investigators in Australia. 17 In an intriguing study, they created a model to compare interventions for STEMI system building using Geographical Information Systems to analyze hospital location, population distribution, road network data, and estimated travel times. In Australia, only 12% of hospitals have primary PCI capability, yet this analysis showed that 93% of the population has timely access to some form of reperfusion therapy, mainly fibrinolytic therapy (for 53% of the population).…”
Section: Articles See P 423 429 437mentioning
confidence: 99%
“…One option would be to increase the number of PCI-capable hospitals. The analysis by Ranasinghe et al 17 suggests that this option would not improve access to timely primary PCI. In fact, from 2001 to 2006, the proportion of US hospitals with PCI capability increased by 44% (from 25.5% of hospitals to 36.2%), yet the percentage of the population residing within 60 minutes of a PCI-capable hospital only increased by 0.9%.…”
Section: Articles See P 423 429 437mentioning
confidence: 99%